Evaluation of Efflux-Mediated Resistance and Biofilm formation in Virulent Pseudomonas aeruginosa Associated with Healthcare Infections - Paul A. Akinduti; Onome W. George; Hannah U. Ohore; Olusegun E. Ariyo; Samuel T. Popoola; Adenike I. Adeleye; Kazeem S. Akinwande; Jacob O. Popoola; Solomon O. Rotimi; Fredrick O. Olufemi; Conrad A. Omonhinmin; Grace I. Olasehinde (MDPI AG, 2023)
Pseudomonas aeruginosa is a significant pathogen identified with healthcare-associated infections. The present study evaluates the role of biofilm and efflux pump activities in influencing high-level resistance in virulent P. aeruginosa strains in clinical infection. Phenotypic resistance in biotyped Pseudomonas aeruginosa (n = 147) from diagnosed disease conditions was classified based on multiple antibiotic resistance (MAR) indices and analysed with logistic regression for risk factors. Efflux pump activity, biofilm formation, and virulence factors were analysed for optimal association in Pseudomonas infection using receiver operation characteristics (ROC). Age-specificity (OR [CI] = 0.986 [0.946-1.027]), gender (OR [CI] = 1.44 [0.211-9.827]) and infection sources (OR [CI] = 0.860 [0.438-1.688]) were risk variables for multidrug resistance (MDR)-P. aeruginosa infection (p < 0.05). Biofilm formers caused 48.2% and 18.5% otorrhea and wound infections (95% CI = 0.820-1.032; p = 0.001) respectively and more than 30% multidrug resistance (MDR) strains demonstrated high-level efflux pump activity (95% CI = 0.762-1.016; p = 0.001), protease (95% CI = 0.112-0.480; p = 0.003), lipase (95% CI = 0.143-0.523; p = 0.001), and hemolysin (95% CI = 1.109-1.780; p = 0.001). Resistance relatedness of more than 80% and 60% to cell wall biosynthesis inhibitors (ceftazidime, ceffproxil, augumentin, ampicillin) and, DNA translational and transcriptional inhibitors (gentamicin, ciprofloxacin, ofloxacin, nitrofurantoin) were observed (p < 0.05). Strong efflux correlation (r = 0.85, p = 0.034) with MDR strains, with high predictive performances in efflux pump activity (ROC-AUC 0.78), biofilm formation (ROC-AUC 0.520), and virulence hierarchical-clustering. Combine activities of the expressed efflux pump and biofilm formation in MDR-P. aeruginosa pose risk to clinical management and infection control.